METHODOLOGICAL APPROACHES IN EDUCATING THE RAPID FORCE MOBILISATION CAPACITY OF SKI JUMPERS - Wilhelm Robert GROSZ (Editura Universitatii Transilvania din Brasov, 2019)
This study was conceived to bring a new orientation in the ski jumping training process addressing psychomotor quality, especially to its component - rapid force. The fast force education requires a new approach of the training process according to the technical components specificity and related to the individual particularities. The rapid force manifestation in symbiosis with de second phases in ski jumping and the takeoff movement ensures a fast entry into the flight phase with an optimal trajectory under a right timing. The research was conducted on young athletes - three components of the national ski jumping team aged 13-14 years - and targeted the rapid force as physical component. After applying the bi-cycle planned of rapid force development methodology, the results obtained provide more confidence in the effectiveness of the training and a positive prognosis regarding the results to be obtained in this field.